PERANCANGAN SISTEM INFORMASI PERSEDIAAN OBAT PADA APOTEK RUMAH SAKIT MENGGUNAKAN METODE SPIRAL - Ricky Imanuel Ndaumanu (J-Icon : Jurnal Komputer dan Informatika, 2020)
Pharmacy is a place to sell and sometimes make or mix drugs. A pharmacy is also a place where pharmacists practice the pharmaceutical profession. Many patients complained that the available drugs are incomplete, because the system used is still manual, in this case still using the ledger format to see the available drug supplies. In this case, problems in the drug data collection system and drug inventory data collection are sometimes constrained in determining the stock and the amount of drugs available at the pharmacy. Therefore it is necessary to conduct an evaluation study to collect data on the supply of drugs in hospital pharmacies in order to identify the cause of out of stock and drug supply in hospital pharmacies, determine the amount in stocking of drugs and determine Production Correction Factors for each drug submitted by the manufacturer. To overcome this problem, we need an application or desktop-based system that can evaluate and determine the available inventory at hospital pharmacies. The methodology used in the development of this information system is the Spiral method, which Spiral model is one form of evolution that uses the natural iteration method which is owned by the prototyping model and combined with the systematic aspects developed with the waterfall model. Entities contained in this information system are suppliers, pharmacists, patients and leaders.